Role of Nutrition in Oral Health - Aravindha Babu.N1 , Nishanth.G2 , B. Krishna Prasanth3 , K.M.K.Masthan4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
There is a mutually beneficial relationship present between the well being of oral tissues and nutrition in ourbody. The health of the oral tissues, the quality of saliva in mouth, the count of oral tissues and the extentof the taste relies on the consumption of nutrients. Oral health denotes the kind of food that has been takenand also the level of nutrients. A review of literary study was made to describe briefly about this mutuallybeneficial relationship.